Assertive communication and teaching performance in the educational institution N° 2040 Republic of Cuba – comas, 2022 - Vela Alquizar, Zoila (2023)
The proposal of this study determines the relationship between asertive communication and educational desire; The study was carried out at the Educational Institute no. 2040 Republic of Cuba, Comas District; The study population was 47 students and the study period was 2022. This study was carried out through quantitative methods using a related design, a non-experimental, cross-sectional research framework; This work is guided by a theoretical framework developed from a pedagogical perspective on safe and educational communication. The instrument is applied to the population and responds to 48 predetermined divisions in variable doses, each with four dimensions and one dimension with six respondents; The data show that both academic performance and assertive communication are at a high level. The conclusion we reached is that there is a significant level in both cases. Finally, we can conclude that there is some correlation between learning performance and secure communication, and this correlation is significant, positive and direct.